Presleep Arousal and Sleep in Early Childhood. Issue 4 (4th July 2021) - Hoyniak, Caroline P.; McQuillan, Maureen M.; Bates, John E.; Staples, Angela D.; Schwichtenberg, A. J.; Honaker, Sarah M.
Abstract: Research suggests that arousal during the transition to sleep—presleep arousal—is associated with sleep disturbances. Although a robust literature has examined the role of presleep arousal in conferring risk for sleep disturbances in adults, substantially less research has examined the developmental origins of presleep arousal in early childhood. The authors examined presleep arousal using parent report and psychophysiological measures in a sample of preschoolers to explore the association between different measures of presleep arousal, and to examine how nightly presleep arousal is associated with sleep. Participants included 29 children assessed at 54 months of age. Presleep arousal was measured using parent reports of child arousal each night at bedtime and using a wearable device that took minute-by-minute recordings of heart rate, peripheral skin temperature, and electrodermal activity each night during the child's bedtime routine. This yielded a dataset with 4, 550 min of ambulatory recordings across an average of 3.52 nights per child ( SD = 1.84 nights per child; range = 1–8 nights). Sleep was estimated using actigraphy. Findings demonstrated an association between parent-reported and psychophysiological arousal, including heart rate, peripheral skin temperature, and skin conductance responses during the child's bedtime routine. Both the parent report and psychophysiological measures of presleep arousal showed some associations with poorer sleep, with the most robust associations occurring between presleep arousal and sleep onset latency. Behavioral and biological measures of hyperarousal at bedtime are associated with poorer sleep in young children. Findings provide early evidence of the utility of wearable devices for assessing individual differences in presleep arousal in early childhood.